1991
DOI: 10.1002/j.1460-2075.1991.tb08024.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of the CD4 and CD8 lineage of T cells: instruction versus selection.

Abstract: T cells bearing the alpha beta T cell receptor (TCR) can be divided into CD4+8‐ and CD4–8+ subsets which develop in the thymus from CD4+8+ precursors. The commitment to the CD4 and CD8 lineage depends on the binding of the alpha beta TCR to thymic major histocompatibility complex (MHC) coded class II and class I molecules, respectively. In an instructive model of lineage commitment, the binding of the alpha beta TCR, for instance to class I MHC molecules, would generate a specific signal instructing the CD4+8+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
70
1

Year Published

1991
1991
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(76 citation statements)
references
References 28 publications
5
70
1
Order By: Relevance
“…More recent modeling emphasizes the strength and͞or duration of TCR-based signals (13,53). According to the strength of signal model, increased signaling through CD4-class II interactions promotes CD4 lineage commitment, whereas weaker signals underlie a CD8 default pathway (52,54,55). Our experiments do not distinguish between the impact of MHC class II-and class I-dependent signaling in early lineage commitment.…”
Section: Discussionmentioning
confidence: 61%
“…More recent modeling emphasizes the strength and͞or duration of TCR-based signals (13,53). According to the strength of signal model, increased signaling through CD4-class II interactions promotes CD4 lineage commitment, whereas weaker signals underlie a CD8 default pathway (52,54,55). Our experiments do not distinguish between the impact of MHC class II-and class I-dependent signaling in early lineage commitment.…”
Section: Discussionmentioning
confidence: 61%
“…One model is that overexpression of AML1 might have redirected the fate of otherwise CD4 SP-oriented DP thymocytes into the CD8 SP lineage. According to the instruction model, the affinities of the TCR for class II and class I molecules guide the differentiation of DP cells into the CD4 SP and CD8 SP lineages, respectively (31,32). It is hypothesized that DP cells receive signals from their CD4/TCR or CD8/TCR molecules and distinguish each signal based on its strength and duration (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…This could be a mechanism to prevent the activation of DP thymocytes before selection has taken place. (3,32,33,45,55,57,62) as well as MHC class II-and class I-deficient mice (10, 16) has shown that this decision is mediated by positive selection that is dictated by the interaction of a specific TcR, associated with a CD4 or CD8 coreceptor, with the appropriate positive-selecting MHC class II or class I, respectively, on epithelial cells of the thymus.Two models of thymocyte selection have been proposed to explain the decision of a DP cell to commit to the CD4 or CD8 lineage (6,50,66), although this question is still open. The instructive model proposes that positive selection occurs at the DP stage of maturation.…”
mentioning
confidence: 99%
“…Two models of thymocyte selection have been proposed to explain the decision of a DP cell to commit to the CD4 or CD8 lineage (6,50,66), although this question is still open. The instructive model proposes that positive selection occurs at the DP stage of maturation.…”
mentioning
confidence: 99%